A MODEL OF THE STRUCTURAL STRUCTURE OF PEDAGOGICAL STRUCTURING OF EDUCATION IN THE CONTEXT OF DIGITAL TECHNOLOGIES - Ergashev Nuriddin Gayratovich (American Journals, 2023)
This article presents a theoretical analysis of the model of the structural structure of pedagogical structuring of education in the context of digital technologies. Despite the growing interest in the hierarchical teaching of the course of technical systems in various areas of specialization of an informed society in the context of digital technologies, in the current period there are several practices of its implementation in the process of teaching this course in higher education institutions. These aspects will be analyzed below.
Keywords: Digital technologies, pedagogical structuring of Education, dynamic education, reverse educational structuring model, etc.